Response rate and local recurrence after concurrent immune checkpoint therapy and radiotherapy for non–small cell lung cancer and melanoma brain metastases. Issue 24 (14th September 2020) - Qian, Jack M.; Martin, Allison M.; Martin, Kate; Hammoudeh, Lubna; Catalano, Paul J.; Hodi, F. Stephen; Cagney, Daniel N.; Haas‐Kogan, Daphne A.; Schoenfeld, Jonathan D.; Aizer, Ayal A.
Abstract : Background: Prior literature has suggested synergy between immune checkpoint therapy (ICT) and radiotherapy (RT) for the treatment of brain metastases (BrM), but to the authors' knowledge the optimal timing of therapy to maximize this synergy is unclear. Methods: A total of 199 patients with melanoma and non–small cell lung cancer with BrM received ICT and RT between 2007 and 2016 at the study institution. To reduce selection biases, individual metastases were included only if they were treated with RT within 90 days of ICT. Concurrent treatment was defined as RT delivered on the same day as or in between doses of an ICT course; all other treatment was considered to be nonconcurrent. Multivariable Cox proportional hazards models were used to assess time to response and local disease recurrence on a per‐metastasis basis, using a sandwich estimator to account for intrapatient correlation. Results: The final cohort included 110 patients with 340 BrM, with 102 BrM treated concurrently and 238 BrM treated nonconcurrently. Response rates were higher with the use of concurrent treatment (70% vs 47%; P < .001), with correspondingly lower rates of progressive disease (5% vs 26%; P < .001). On multivariable analysis, concurrent treatment was found to be associated with improved time to response (hazard ratio, 1.76; 95% CI, 1.18‐2.63 [ P = .006]) and decreased local recurrence (hazard ratio, 0.42; 95% CI, 0.23‐0.78 [ P = .006]). This effect appeared to be greater for melanoma than for non–small cell lung cancer, although interaction tests were not statistically significant. Only 1 of 103 metastases which had a complete response later developed disease progression. Conclusions: Concurrent RT and ICT may improve response rates and decrease local recurrence of brain metastases compared with treatment that was nonconcurrent but delivered within 90 days. Further study of this combination in prospective, randomized trials is warranted. Abstract : There is significant interest in potential synergy between radiotherapy and immune checkpoint therapy, but the optimal timing of each therapy remains unclear. The current study examines a cohort of patients with melanoma and non–small cell lung cancer with brain metastases who were managed with immune checkpoint therapy and brain‐directed radiotherapy within a 90‐day period. Compared with nonconcurrent therapy, concurrent therapy is associated with an improved brain metastasis response rate and decreased local recurrence.